Land As The Soul Of The Nation: Implications Of The Transitions Of Land Status In The Talang Mamak Customary Law Community - Hengki Firmanda; Mahmud Hibatul Wafi; Mark Wodward; Erlies Septiana Nurbani; Sudjito; Dina Imam Supaat (USIM PRESS, 2024)
Malaysian Journal of Syariah and Law (MJSL) Volume 12 Issue 1 Page (148-156)